The burden of conscientiousness?: examining brain activation and cortisol response during social evaluative stress - Dahm, Anne-Sophie; Kirsch, Peter (Psychoneuroendocrinology, 2017)
Although conscientiousness has for a long time been considered generally adaptive, there are findings challenging this view, suggesting that conscientiousness might be less advantageous during uncontrollable stress. We here examined the impact of conscientiousness on brain activation during and the cortisol response following an uncontrollable social evaluative stress task in order to test this hypothesis. Brain activation and cortisol levels were measured during an fMRI stress task, where subjects (n=86) performed cognitive tasks containing preprogrammed failure under time pressure, while being monitored by a panel of experts inducing social-evaluative threat. The degree of conscientiousness was measured using the NEO-FFI. We observed a positive correlation between conscientiousness and salivary cortisol levels in response to the stressful task in male subjects only. In male subjects conscientiousness correlated positively with activation in right amygdala and left insula, and, moreover, mediated the influence of amygdala and insula activation on cortisol output. This pattern of brain activation can be interpreted as a disadvantageous response to uncontrollable stress to which highly conscientious individuals might be predisposed. This is the first study showing the effect of conscientiousness on physiology and brain activation to an uncontrollable psychosocial stressor. Our results provide neurobiological evidence for the hypothesis that conscientiousness should not just be seen as beneficial, but rather as a trait associated with either costs or benefits depending on the extent to which one is in control of the situation.